1982
DOI: 10.1007/bf00347866
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of 4,4?-MethyIenedianiline Derivatives in the Salmonella histidine reversion assay

Abstract: 4,4'-Methylenedianiline and its derivatives were assayed for mutagenicity in the Salmonella/microsomal mutagenicity assay develop by Ames. A specificity to revert strain TA98 suggests a mechanism of frameshift mutagenesis. Liver microsomal preparations (S-9) from rats induced with phenobarbital were most effective for metabolic activation. Alkyl substitution of 4,4'-methylenedianiline did not alter its mutagenic activity; however, substitution of both positions ortho to the amino group eliminated mutagenic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 11 publications
(9 reference statements)
0
19
0
Order By: Relevance
“…Because of the substantial amount of free MDA present in the traditional hand-layup of high performance composites substituting a non-toxic diamine for MDA could greatly reduce the need for personnel protection. It has been suggested that MDA's physical size and relative planarity allows it to intercalate into the DNA molecule, interfering with transcription and thereby causing mutations [4][5][6]. The diamines chosen for this study represent different ideas about how to modify the structure to prevent the mutagenic effects of MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the substantial amount of free MDA present in the traditional hand-layup of high performance composites substituting a non-toxic diamine for MDA could greatly reduce the need for personnel protection. It has been suggested that MDA's physical size and relative planarity allows it to intercalate into the DNA molecule, interfering with transcription and thereby causing mutations [4][5][6]. The diamines chosen for this study represent different ideas about how to modify the structure to prevent the mutagenic effects of MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of functional groups ortho to the amino groups could alter 4,4'-methylenedianiline's mutagenicity (Rao et al, 1982), but substitution with alkyl or alkoxycarbonyl groups did not affect or reduce 4,4'-methylenedianiline mutagenicity in TA98. However, the substitution with chlorine or fluorine enhanced mutagenicity.…”
Section: Discussionmentioning
confidence: 99%
“…4,4'-Methylenedianiline's mutagenic activity has been compared with that of other aromatic amines (Lavoie et al, 1979;Rao et al, 1982), antithyroid agents and thyroid carcinogens (Oppenheimer, 1979), and carcinogenic aromatic amines (Miller, 1978). 4,4'-Methylenedianiline has been included in structure-activity studies in which the atoms linking the aniline moieties were varied (Lavoie et al, 1979) and the chemical analogs were tested in Salmonella typhimurium TA98 and TA100.…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborate those of Shahin [86] who had earlier indicated an inverse relationship between mutagenicity and the size of the alkyl/alkoxy substituent at position C-1 of 2,4-diaminoalkyl(or alkoxy)benzenes. However, deactivating effects were observed by Rao et al when methyl/ethyl groups were substituted on both sides of NH 2 groups as in the case of methylenedianiline derivatives as illustrated by reduced mutagenicity of 4,4 0 -methylenebis(2-methyl-6-ethylaniline) and 4,4 0 -methylenebis(2,6-diethylaniline) relative to their non-alkylated analogues [93].…”
Section: Adductmentioning
confidence: 93%